Documenting the Architecture of Ramses Wissa Wassef: The Case for the Vernacular - Daniel Ayad (Journal of Traditional Building, Architecture and Urbanism, 2022)
Conchita Añorve-Tschirgi, Ehsan Abushadi The Architecture of Ramses Wissa Wassef AUC Press, 2020